2015
DOI: 10.1039/c4lc01465k
|View full text |Cite
|
Sign up to set email alerts
|

Optofluidic ultrahigh-throughput detection of fluorescent drops

Abstract: a This paper describes an optofluidic droplet interrogation device capable of counting fluorescent drops at a throughput of 254 000 drops per second. To our knowledge, this rate is the highest interrogation rate published thus far. Our device consists of 16 parallel microfluidic channels bonded directly to a filtercoated two-dimensional Complementary Metal-Oxide-Semiconductor (CMOS) sensor array. Fluorescence signals emitted from the drops are collected by the sensor that forms the bottom of the channel. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(82 citation statements)
references
References 28 publications
0
82
0
Order By: Relevance
“…7, 8, 10, 11, 40, 41 Indeed, the conventional methods including RT-PCR typically require sample preparation or conducted in buffer with typical LOD of 10 3 copies/mL. 18, 34 In addition, compared to other 1D on-chip 7, 42, 43 or 2D droplet detection systems 14, 15 such as wide-field fluorescence imaging, the major advantages of our simple 3D particle counter include 1) high throughput: 100,000s droplets/s or an effective volume of observation of 0.1 ml/min, which allows us to rapidly interrogate a large volume (mL) of droplets, and 2) robustness: the detection of a ‘hit’ is defined by a pattern recognition algorithm 20 besides threshold intensity that alone often suffers from higher false-positive/negative rates. 23, 24 Additionally, our IC 3D can distinguish single molecules because IC 3D operates using “digital” measurements, which droplets are counted as either ‘0 (negative)’ or ‘1 (positive)’.…”
Section: Discussionmentioning
confidence: 99%
“…7, 8, 10, 11, 40, 41 Indeed, the conventional methods including RT-PCR typically require sample preparation or conducted in buffer with typical LOD of 10 3 copies/mL. 18, 34 In addition, compared to other 1D on-chip 7, 42, 43 or 2D droplet detection systems 14, 15 such as wide-field fluorescence imaging, the major advantages of our simple 3D particle counter include 1) high throughput: 100,000s droplets/s or an effective volume of observation of 0.1 ml/min, which allows us to rapidly interrogate a large volume (mL) of droplets, and 2) robustness: the detection of a ‘hit’ is defined by a pattern recognition algorithm 20 besides threshold intensity that alone often suffers from higher false-positive/negative rates. 23, 24 Additionally, our IC 3D can distinguish single molecules because IC 3D operates using “digital” measurements, which droplets are counted as either ‘0 (negative)’ or ‘1 (positive)’.…”
Section: Discussionmentioning
confidence: 99%
“…12 The maximum acquisition rate of the sensor, which can be upgraded over time with faster sensors, could detect 40-pL droplets at 254 kHz. The system accurately measured “hit” droplet concentration from 1 per million to 1 per hundred; beyond this, the presence of multiple adjacent fluorescent droplets obscures the measurement due to the 2-fold variance in droplet velocity in the detection region.…”
Section: The Front-end Of Discovery: More Fastermentioning
confidence: 99%
“…For the serial interrogation of the sample at 10 cfu/ml, we counted a total of 1 ml of drops, which took about 1 h. We have recently shown that it is possible to count drops in massively parallel format at a rate of $0.25 million drops/second. 36 Given this rate, it would require only 2 min to interrogate 1 ml of sample. The assay would then be rate-limited by the kinetics of the probe and the enzyme.…”
Section: Dynamic Range Of Our Methodsmentioning
confidence: 99%